RADIOMETRIC CALIBRATION OF VISIBLE CHANNEL 1 AND 2 OF SENSOR AVHRR/2 OF SATELLITE IN NOAA-14 POLAR ORBIT FOR ESTIMATING OF NDVI - Rojas Acuña, Joel (2000)
The calibration of the original HRPT and LAC images, corresponding to channels 1 and 2 of the AVHRR sensor of the NOAA-14 satellite in polar orbit has been undertaken with the purpose of estimating the Normalized Difference Vegetation Index (NDVI) above Peru. The imagery data used were obtained from IMARPE, ABTEMA, INPE and SAA, and are in binary 16 bits per pixel format for the 5 channels. Reflectance images for channels 1 and 2 images have been obtained in 16 bits (data type: integers). Afterwards, the NDVI is obtained using an equation in which the information from the reflectance images is used. The imagery data product of the vegetation indices are obtained for every day from January to Febrary 1999. We pretend to obtain monthly and 10-day images to get an average NDVI using the method of compound máxima. Finally, we are preparing a time series for this parameter from January 1980 until June 2001.